2022
DOI: 10.21203/rs.3.rs-1342433/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antenna movements as a function of odorants’ biological value in honeybees (Apis mellifera L.)

Abstract: In honeybees, the antennae are highly mobile sensory organs that express scanning movements in various behavioral contexts and toward many stimuli, especially odorants. The rules underlying these movements are still unclear. Using a motion-capture system, we analyzed bees’ antennal responses to a panel of pheromonal and other biologically relevant odorants. We observed clear differences in bees’ antennal responses, with opposite movements to stimuli related to opposite contexts: slow backward movements were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…This result seems to contradict the study by Cholé et al, in which no change in antennal orientation was found in response to aversive conditioned odors ( Cholé et al, 2015 ). However, recently, Cholé et al have deepened their former study extending their analysis to different odors, reporting that aversive pheromones (including 2-heptanone) elicit backward movements, in agreement with our present work ( Cholé et al 2022 ). Although it might be inaccurate to differentiate innate from learned behaviors ( Gorostiza, 2018 , Mameli and Bateson, 2006 ), it should be noted that 2-heptanone is an odor with a strong innate relevance in the wild and, therefore, is possible that honey bees have been previously exposed to it before their capture.…”
Section: Discussionsupporting
confidence: 92%
“…This result seems to contradict the study by Cholé et al, in which no change in antennal orientation was found in response to aversive conditioned odors ( Cholé et al, 2015 ). However, recently, Cholé et al have deepened their former study extending their analysis to different odors, reporting that aversive pheromones (including 2-heptanone) elicit backward movements, in agreement with our present work ( Cholé et al 2022 ). Although it might be inaccurate to differentiate innate from learned behaviors ( Gorostiza, 2018 , Mameli and Bateson, 2006 ), it should be noted that 2-heptanone is an odor with a strong innate relevance in the wild and, therefore, is possible that honey bees have been previously exposed to it before their capture.…”
Section: Discussionsupporting
confidence: 92%
“…Our first aim was to investigate how antennal movement participates in spatial sampling. It has recently been shown that honeybees orient their antennae towards appetitive odour sources and away from aversive ones (Cholé et al 2022;Gascue et al 2022). Moreover, the analysis demonstrated a general trend of positive correlation between the time the antennae spent focused on an odour target and its valence (Gascue et al 2022).…”
Section: Exploration-exploitation Trade-offmentioning
confidence: 82%